The IL-23/IL-22/IL-18 axis in murine Campylobacter jejuni infection. Issue 1 (December 2016) - Heimesaat, Markus; Grundmann, Ursula; Alutis, Marie; Fischer, André; Göbel, Ulf; Bereswill, Stefan
Abstract Background HumanCampylobacter jejuni infections are worldwide on the rise. Information about the distinct molecular mechanisms underlying campylobacteriosis, however, are scarce. In the present study we investigated whether cytokines including IL-23, IL-22 and IL-18 sharing pivotal functions in host immunity were involved in mediating immunopathological responses uponC. jejuni infection. Results To address this, conventionally colonized IL-23p19−/−, IL-22−/− and IL-18−/− mice were perorally infected withC. jejuni strain ATCC 43431. Respective gene-deficient, but not wildtype mice were susceptible toC. jejuni infection and could be readily colonized with highest pathogenic loads in the terminal ileum and colon at day 14 postinfection (p.i.). In IL-23p19−/−, IL-22−/− and IL-18−/− mice viableC. jejuni were detected in MLNs, but did not translocate to spleen, liver, kidney and blood in the majority of cases. Susceptible IL-22−/−, but neither IL-23p19−/−, nor IL-18−/− mice harbored higher intestinal commensalE. coli loads when compared to resistant wildtype mice. AlikeC. jejuni, commensalE. coli did not translocate from the intestinal to extra-intestinal tissue sites. DespiteC. jejuni infection, mice lacking IL-23p19, IL-22 or IL-18 exhibited less apoptotic cells, but higher numbers of proliferating cells in their colonic epithelium as compared to wildtype mice at day 14 p.i. Less pronounced apoptosis was parallelled by lower abundance of neutrophils within the colonic mucosa and lamina propria of infected IL-23p19−/− and IL-22−/− as compared to wildtype control mice, whereas less distinct colonic TNF secretion could be measured in IL-22−/− and IL-18−/− than in wildtype mice at day 14 p.i. Notably, in infected IL-22−/− mice, colonic IL-23p19 mRNA levels were lower, whereas the other way round, colonic IL-22 expression rates were lower in IL-23p19−/− mice as compared to wildtype controls. Moreover, IL-18 mRNA was less distinctly expressed in large intestines of naive and infected IL-22−/− mice, but not vice versa, given that IL-22 mRNA levels did not differ between in IL-18−/− and wildtype mice. Conclusion Cytokines belonging to the IL-23/IL-22/IL-18 axis mediate immunopathological responses upon murineC. jejuni infection in a differentially orchestrated manner. Future studies need to further unravel the underlying regulatory mechanisms orchestrating pathogenic-host interaction.